1987
DOI: 10.1111/j.1600-0609.1987.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil dysfunctions in thalassaemia major: The role of cell iron overload

Abstract: The susceptibility to infections was recorded in 13 patients with I3 thalassaemia major (T.P.). The following parameters were also investigated in their polymorphonuclear neutrophils (PMN): nitro blue tetrazolium (NBT) reduction, heated yeast and Escherichia coli phagocytosis, Escherichia coli killing and myeloperoxydase activity. These results were compared to those obtained in healthy controls (H.C.). The Perk's reaction was performed on PMN and graded according to a scoring system with the aim of quantifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 31 publications
0
17
1
1
Order By: Relevance
“…A number of investigators have shown that ingestion of C. albicans by PMNs of thalassemia patients was normal (17–19). However, these data were different from others who utilized Escherichia coli , baker's yeast (16, 20, 21), Salmonella typhi , and Staphylococcus aureus (22). The differences could be due to the use of different kinds of organisms and different methodologies used in these experiments.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…A number of investigators have shown that ingestion of C. albicans by PMNs of thalassemia patients was normal (17–19). However, these data were different from others who utilized Escherichia coli , baker's yeast (16, 20, 21), Salmonella typhi , and Staphylococcus aureus (22). The differences could be due to the use of different kinds of organisms and different methodologies used in these experiments.…”
Section: Discussioncontrasting
confidence: 70%
“…Our whole blood study used 40–50% of autologous plasma which not only mimics the plasma concentration in vivo, but also contains enough opsonins and other physiological concentration of factors such as extracellular calcium for such initiation process. Study in thalassemia patients showed that 10–20% of autologous serum or plasma was enough to obtain maximum phagocytosis and intracellular killing of Escherichia coli and yeast cells (16). This assay should provide an improved physiological milieu to include the presence of soluble factors necessary for opsonization of microorganisms and regulation of PMN function.…”
Section: Discussionmentioning
confidence: 99%
“…It was established that iron and its protein compounds have immunoregulatory characters, and therefore, an excess of iron may adversely affect the immune balance [37]. Numerous studies have shown the negative effect of excess iron on immunological functions, which include suppression of monocyte-macrophage system, changes in subpopulations of T-lymphocytes increasing CD8 and suppression of CD4, increased secretion of immunoglobulins and inhibiting the function of the complement system [16,[37][38][39].…”
Section: Iron Overloadmentioning
confidence: 99%
“…In addition, phagocytosis of microorganisms, dyserythroportic precursors and aging or damaged red blood cells (inside and/or outside the vessel) produces oxidative stress [40]. The fact that the excess of iron has a negative effect on the function of PMN and inhibites phagocytosis indicated above [13,14,[16][17][18].…”
Section: Iron Overloadmentioning
confidence: 99%
See 1 more Smart Citation